Analyzing financial development's moderating role on the investment-environmental quality nexus: Evidence from Australia using Autoregressive Distributed Lag approach - Ambepitiya Wijethunga Gamage Champa Nilanthi Wijethunga; Mohammad Mafizur Rahman; Tapan Sarker (Environmental and Sustainability Indicators)
Understanding the impact channels of financial development on environmental quality is vital for achieving desired environmental targets. While the direct impact of financial development on environmental quality has been extensively addressed, its indirect channel through investment has not been broadly explored. Thus, how financial development moderates the impact of domestic investments and foreign direct investments on environment can be an important research agenda. Therefore, this research purposes to study whether financial development moderates the impact of investments on environmental quality in Australia for the period from 1980 to 2021 using the Autoregressive Distributed Lag (ARDL) model. The key findings emphasize that financial development degrades environmental quality in Australia. Moreover, foreign direct investments have a positive effect on environmental quality, confirming the validity of the Pollution Halo Hypothesis in Australia. In contrast, domestic investments worsen environmental quality. Additionally, financial development does not mitigate the harmful impact of domestic investments on environmental quality. However, financial development plays a neutral role in moderating the impact of foreign direct investments on environmental quality while moderating the impact of domestic investment-environmetal quality relationship. These empirical findings provide diverse policy implications for ensuring environmental quality in Australia by strategically supporting both foreign and domestic investments.